If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 7 = -4y + -10 Reorder the terms: 7 + 2y = -4y + -10 Reorder the terms: 7 + 2y = -10 + -4y Solving 7 + 2y = -10 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 7 + 2y + 4y = -10 + -4y + 4y Combine like terms: 2y + 4y = 6y 7 + 6y = -10 + -4y + 4y Combine like terms: -4y + 4y = 0 7 + 6y = -10 + 0 7 + 6y = -10 Add '-7' to each side of the equation. 7 + -7 + 6y = -10 + -7 Combine like terms: 7 + -7 = 0 0 + 6y = -10 + -7 6y = -10 + -7 Combine like terms: -10 + -7 = -17 6y = -17 Divide each side by '6'. y = -2.833333333 Simplifying y = -2.833333333
| 2x^5+12x^4+16x^3=0 | | 4-(x+5)=32+x | | 6x+x+3=17 | | 30/12/3 | | 2x-3(4x+1)=-23 | | 150000000/1.12 | | y=4(0.37)+1 | | 19+-4c=17 | | 7x+3(4x+1)=10 | | 4.7x+2=3.7x | | -x-2(5-x)=2+2x-5 | | 5x-[3-2(x-1)]=5x+1 | | 3x-2(x-2)=7 | | x^3-x^2-33x-45=0 | | 4x-3=2(x-9) | | 2x=2.25 | | 4-3y=1200 | | 3(2y)+2y=8 | | x+7=75x-y=5 | | 19x^3+46x^2-46x+45=0 | | 4.6x+2=3.6x | | 9ln(8x)+4=22 | | y=50+4(x) | | 144x^2-675x-225=0 | | 6(t-3)=2(-2t) | | (4/(x+1))=3/x | | h/3-10=-2 | | 8x-5y=45 | | 12x-23=37 | | X(8.2)=20 | | 2e-5=7 | | u/2=75/5 |